Из опыта проверки обратных клапанов на патентную чистоту - Shegelman I. R., Vasilyev A. S., Shchukin P. O. (Priority directions of scienceand education development, 2016)
verification has check valves of pipelines to-infringement. It is shown that during their finalization should be redesigned to check-infringement.
Keywords: патентная чистота; check valves; patent purity; обратные клапаны